(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2023)
The COVID-19 pandemic still imprisons people’s travel in China, which leads to the mental health crisis, especially for students of generation Z. Simultaneously, the staycation which is one of the relatively safe ways of traveling under the epidemic prevention and control have been promoted by the government and received attention. The purpose of this research is to investigate how to make students restore from staycation travel products and promote their study engagement, which is a background of insufficient research in education. Based on the research design of the survey, valid data were collected with an online questionnaire survey among 415 college students studying in Macau and were analyzed. Study findings supported the hypothesized relationships and revealed that a positive relationship between staycation involvement and study engagement of students. In addition, the relationship between staycation involvement and study engagement is mediated by restoration, psychological capital and intrinsic motivation. For university educators, these insights are beneficial in developing innovative instructional approaches to solve issues with students’ mental health. As a consequence, this research spans the social science discilines of psychology, tourism and education. The study’s theoretical and practical implications are discussed.